Two Novel Three‐Dimensional Tetraphenylethylene‐Based Rare Earth MOFs with Ultra‐High Proton Conductivity and Performance Stability. Issue 60 (26th September 2022) - Wang, Shuyu; Zhao, Lijia; Sun, Hanxu; Wu, Yuanyuan; Wang, Ruidong; Zhang, Suoshu; Du, Lin; Zhao, Qi‐Hua
Abstract: In this work, the two example rare earth‐based metal‐organic frameworks (La III ‐based MOFs), Eu‐ETTB and Gd‐ETTB, were obtained by self‐assembly. Both materials showed extremely high proton conductivity, with the proton conductivity of Eu‐ETTB being 1.53×10 −2 S cm −1 at 98 % relative humidity (RH) and 85 °C and that of Gd‐ETTB being 2.63×10 −2 S cm −1 at 98 % RH and 75 °C. This was almost the best performance observed for three‐dimensional porous MOFs without post‐synthetic modification and was based on milder conditions than for most materials. Furthermore, cycle test experiments and continuous work tests showed that both materials had excellent performance both in terms of stability and durability. Water vapor adsorption experiments showed that a large number of water molecules are adsorbed the hydrogen‐bond network's being rebuilt by the adsorbed water molecules in the pore channel and thus optimizing the channels for proton transfer explained the MOF's high performance. Abstract : Eu‐ETTB and Gd‐ETTB were obtained with the same topology by self‐assembly. Both materials showed extremely high proton conductivity: the proton conductivity of Eu‐ETTB was 1.53×10 −2 S cm −1 at 98 % relative humidity (RH) and 85 °C, while Gd‐ETTB had a proton conductivity value of 2.63×10 −2 S cm −1 at 98 % RH and 75 °C. Furthermore, both materials had excellent performance both in terms of stability and durability.